Bi-directional relationships between co-morbid insomnia and sleep apnea (COMISA). (December 2021) - Sweetman, Alexander; Lack, Leon; McEvoy, R Doug; Smith, Simon; Eckert, Danny J.; Osman, Amal; Carberry, Jayne C.; Wallace, Douglas; Nguyen, Phuc D.; Catcheside, Peter
Summary: Insomnia and obstructive sleep apnea (OSA) commonly co-occur. Approximately 30–50% of patients with OSA report clinically significant insomnia symptoms, and 30–40% of patients with chronic insomnia fulfil diagnostic criteria for OSA. Compared to either insomnia or OSA alone, co-morbid insomnia and sleep apnea (COMISA) is associated with greater morbidity for patients, complex diagnostic decisions for clinicians, and reduced response to otherwise effective treatment approaches. Potential bi-directional causal relationships between the mechanisms and manifestations of insomnia and OSA could play an integral role in the development and management of COMISA. A greater understanding of these relationships is required to guide personalized diagnostic and treatment approaches for COMISA. This review summarizes the available evidence of bi-directional relationships between COMISA, including epidemiological research, case studies, single-arm treatment studies, randomized controlled treatment trials, and objective sleep study data. This evidence is integrated into a conceptual model of COMISA to help refine the understanding of potential bi-directional causal relationships between the two disorders. This theoretical framework is essential to help guide future research, improve diagnostic tools, determine novel therapeutic targets, and guide tailored sequenced and multi-faceted treatment approaches for this common, complex, and debilitating condition.